Let Nature Take Its Course: Cultural Adaptation and Pilot Test of Taoist Cognitive Therapy for Chinese American Immigrants With Generalized Anxiety Disorder - Chang, Doris F.; Ng, Nancy; Chen, Teddy; Hung, Tiffany; Miao, Iris Yi; Cao, Yuping; Zhang, Yalin (Frontiers in Psychology, 2020)
This report describes initial results from a multi-stage project to manualize and adapt an indigenous therapy, Chinese Taoist Cognitive Psychotherapy (CTCP), for dissemination in the U.S. context. Study aims were to a) integrate cultural adaptation and implementation science frameworks to manualize and adapt the original intervention, and b) explore the feasibility, acceptability, and effectiveness of the modified intervention, renamed Taoist Cognitive Therapy (TCT), in a sample of Chinese immigrants with generalized anxiety disorder (GAD). Incorporating bottom-up and top-down adaptation approaches, we involved Chinese American clinician stakeholders and experts in Taoist philosophy, cognitive-behavioral therapy, and GAD to help identify cultural and contextual barriers and solutions to enhance treatment acceptability and implementation. Five treatment-seeking Chinese American immigrants (average age= 43.2 years) with a primary diagnosis of GAD completed 14-16 sessions of TCT. Two participants also had secondary diagnoses of major depressive disorder. Changes on primary measures of worry and anxiety were assessed for statistical and clinical significance using reliable change indices (RCI; Jacobson & Truax, 1991) and comparisons to normative data. In this sample of patients with limited prior exposure to Taoism, results found evidence of feasibility and acceptability of the modified intervention, with strong endorsement of Taoist principles at termination. Statistically and clinically significant improvements in anxiety, worry, psychological inflexibility and emotional avoidance were found only for the participants without comorbid depression. Results suggest that Taoist principles of acceptance and flexible adaptation to natural laws may be helpful to Chinese immigrants coping with anxiety. However, additional treatment modifications may be required to address the low self-efficacy and fatalism expressed among those with comorbid depression.